Contribuições para modelagem de alvenaria em blocos de concreto - Pasquantonio, Rafael Dantas (Universidade Federal de São Carlos, 2019)
Masonry is a very widespread construction system around the world, with a great history of use in civilization. However, with the advancement of knowledge, the technique of resolution through the finite element methods arises in the field of engineering. Considering the survey of previous re-search, we can see that a great variety of researches that relate experimental masonry models with finite element solving techniques in commercial software models such as Abaqus. Based on this context, this work aims to characterize the structural masonry elements, and to obtain the parameters for modeling the structural masonry interface of concrete and mortar blocks. A set of tests was carried out to characterize the masonry elements (test of resistance to compression and stress of blocks, mortar and grout) as well as characterization of the interface between block and mortar (bond wrench test, horizontal joint shear test and compression diagonal). From the experimental results, numerical models were developed, using Abaqus/2017 commercial software, to represent the compression behavior of blocks, mortars and grouts. In addition, numerical models of two- and three-block prisms with and without grout were developed as a way of applying the results obtained with respect to the components. After this stage of validation of the numerical models of each of the components, numerical models were developed to represent the interface between block and mortar. In this step the tests of bond wrench test, horizontal joint shear test and diagonal compression were studied. From this analysis, parameters were obtained to represent the plastic behavior of the block, mortar and grout. Nevertheless, parameters for tangential, normal and damage of the interface between block and mortar were reached. Another important point of the research is that the parameters related to the tangential, normal, and damage behavior were able to use the same data to represent the numerical models of the interface representation and only function as a calibration parameter between the different models are the parameters of cohesive behavior (Kn, Ks e Kt).
Contributions for masonry modeling in concrete blocks
Keywords: Alvenaria; Blocos de concreto; Modelagem numérica; Interface; Comportamento coesivo; Masonry; Blocks; Numerical modelling; Interface; Cohesive behavior; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS